Multilayered metamaterials array antenna based on artificial magnetic conductor's structure for the application diagnostic breast cancer detection with microwave imaging. (January 2022) - Zerrad, Fatima-ezzahra; Taouzari, Mohamed; Makroum, El Mostafa; El aoufi, Jamal; Islam, Mohammad Tarikul; Özkaner, Vedat; Abdulkarim, Yadgar I.; Karaaslan, Muharrem
Highlights: Suggested antenna has a wider BW of 7 GHz (4.1–9.7 GHz). Good radiation efficiency of more than 85% and realized gain of 5.1 dBi are obtained. Small size, high gain and UWB capability, the antenna is a strong candidate for MWI applications. The antenna performs admirably in both frequency and time domains with a good fidelity factors of 73% in FtF and acceptable value of 56.7% in SbS . Abstract: In this work, a small multilayer ultra-wideband (UWB) patch antenna for microwave breast imaging (MWI) applications was developed both theoretically and experimentally. However, to improve the antenna performance relating to the bandwidth (BW), the radiating element of the suggested initial antenna is modified by adding a modified split ring resonator (SRR) and slits in the patch as well as the ground plane. Then, to achieve the requisite antenna properties for MWI applications such as the gain and directivity, the antenna is equipped with a uniplanar artificial magnetic conductor (AMC) structure made up of a 3 × 3 array of square modified SRR unit cells. The final proposed prototype has a relatively small size of 20 × 19 × 1.6 mm3 and it accomplishes a return loss below -10 dB (S11< -10 dB) at overall BW of 7 GHz (4.1 – 9.7 GHz) with more than 5 dBi realized gain. In this way, the characteristics of the fabricated antenna are measured to examine the antenna performance. Indeed, the fidelity factor of face-to-face (FtF) and side-by-side (SbS) scenarios are also noticed for the same frequency range. In the final analysis, a simulation model of the antennas, which operate as a transceiver, and a breast phantom model with tumor sample are proposed for detecting cancerous tumor cells within the breast. Hence, the proposed design is suitable in the biomedical applications such as tumor cell detection.